Lessons for Tuberculosis from scrutiny of HIV/AIDS and Malaria UK Parliamentary Questions. (March 2015) - Oliver, Matt; Craig, Gillian M.; Zumla, Alimuddin
Abstract: Objectives: To identify whether parliamentary scrutiny, in the form of Written Parliamentary Questions (WPQs), has any significant impact on the UK government's stated aid priorities and whether, by refining the approach that MPs with an interest in TB take to scrutinising the government on its aid priorities, more resources could be secured for TB. Methods: We downloaded 19, 234 Written Parliamentary Questions directed at the Department for International Development posed by Members of Parliament between June 2001 and September 2014. We categorised questions by theme, party of questioner, geographical area, date and government. We then identified questions which specifically referenced HIV, TB and Malaria, or the Global Fund to Fight Aids, TB and Malaria. Analyses were conducted on each of these categorisations to identify trends which could account for differences in government funding between the three diseases. Results: A significantly greater number of questions were posed on HIV than on TB and Malaria. These questions were more likely to reference a specific geographical area, and come from a wider group of MPs. A broadly equivalent number of questions were asked on TB and Malaria although there were differences between the parties of the MPs tabling questions. We also identified a significant fall in the number of WPQs tabled from the Labour government of 2005–2010 and the Coalition Government of the present day. Conclusion: High volumes of WPQs targeting specific policy areas or geographical locations can play a role in increasing political commitment within government towards a certain disease or condition, however other factors, including high-level MP champions and party policy, can play an equally significant role. Nonetheless, evidence suggests that a broad base of political support (as manifested through WPQs) is important to motivating a government response to a health issue and that the TB community should devote more effort to mobilising this wide political support.